Numeracy across field-dependent and field-independent cognitive styles of junior high students in Indonesia - Aloisius Loka Son; Hendrika Bete; Cecilia Novianti Salsinha (Universitas Hamzanwadi, 2026)
This study explores differences in numeracy between junior high school students with Field-Dependent (FD) and Field-Independent (FI) cognitive styles. Using a qualitative descriptive approach, the study was conducted in two junior high schools in Kefamenanu, West Timor, Indonesia. Forty students, evenly distributed across the two schools, participated in the study. Data were collected through numeracy tests and in-depth interviews to examine students’ performance across three numeracy components: understanding, application, and reasoning. The findings reveal that students with an FI cognitive style generally demonstrated competence in all three components, although some experienced difficulties in reasoning tasks requiring critical evaluation and formal justification. In contrast, students with an FD cognitive style tended to achieve only the understanding and application components and faced persistent challenges in progressing to the reasoning component. These results highlight the importance of differentiated numeracy instruction. FD students benefit from visual representations, explicit guidance, and collaborative learning to strengthen foundational, whereas FI students require non-routine and argumentative tasks to enhance higher-order reasoning. This study recommends that educators and future researchers implement inclusive numeracy literacy practices aligned with students’ cognitive styles.